PSYCHOLOGICAL RESILIENCE AS A PREREQUISITE FOR PRESERVING THE MOTIVATIONAL POTENTIAL OF FUTURE MANAGERS IN CRISIS SITUATIONS - Tetiana Shcherban; Iryna Bretzko; Roman Bizhko; Volodymyr Voitovych (Психологічні перспективи)
Purpose. To identify and justify the role of psychological resilience as a prerequisite for maintaining the motivational potential and self-efficacy of future managers under crisis conditions.